Design and Evaluation for C02 Laser Focus System for use in Treating the Skin Diseases. - AlhamÂ·adani, A. H.; Abdul-Hussin, R. S.; Aljumaily, A. R.; Awad, W.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Due  to  the  importance  of  Laser  usage  in  the  field  of  skin diseases  Like  removing.  the cicatrix  (acne  causes).  skin  lines,  cone spots,  two laser systems  have underwent a study and  evaluation for their use in treatingthe skin diseases.The   research  deals  with  desigrrating  an  optical  system  .The system is for concentrating  the laser beam C02 with a wave length of10.6   micrometer   Descriptions   of  1he  system  and   value   of   theperfonnance  by using the optical design program ZEMAX, operations to   get   a   favorable   design   and   a   center   of   0.005   micrometer Respectively in laboratory temperatttr.\vhich is appropriate for use in treating the skin diseases.